Factors affecting quality of life in connective tissue disease-related interstitial lung disease - Lanier L. O’Hare; Anand S. Iyer; Kathleen O. Lindell; Pariya L. Wheeler; Liang Shan; Tracy Luckhardt; Marie Bakitas (PLoS ONE, 2025)
Background Connective tissue disease-related interstitial lung disease (CTD-ILD) results in an unrelenting symptom burden and may progress to death. The morbidity and mortality associated with CTD-ILD likely has a profound impact on individuals’ health-related quality of life (HRQOL). The factors associated with HRQOL in other chronic lung diseases have been described, but because of the different clinical and demographic characteristics of CTD-ILD, it is unknown if these same factors are associated with HRQOL in CTD-ILD. Research questions What is the association between patient demographic and disease characteristics, symptoms, and HRQOL in CTD-ILD? Study design and methods A cross-sectional design was used to describe HRQOL in CTD-ILD utilizing a secondary data analysis from the Pulmonary Fibrosis Foundation Patient Registry (PFFPR). Data extracted included demographic (age, gender, and race) and disease characteristics [type of CTD-ILD, duration of disease, forced vital capacity (FVC), supplemental oxygen, immunosuppressant medication use, and pulmonary rehabilitation]. Questionnaires were used to evaluate HRQOL and symptoms of shortness of breath, cough, and fatigue. Results The majority of participants were female (66%), white (78%), had a disease duration of 1–3 years (30%), had scleroderma (25%). The average age was 61 years and FVC of 67% predicted. The majority of participants were not on supplemental oxygen (62%), taking immunosuppressive medications (66%), or active in pulmonary rehabilitation (89%). Female gender, lower FVC, supplemental oxygen use, pulmonary rehabilitation participation, shortness of breath, cough, and fatigue were all correlated with poorer HRQOL. Shortness of breath mediated the relationships between HRQOL and the factors of gender, FVC, supplemental oxygen use, and pulmonary rehabilitation. Fatigue mediated the relationship between HRQOL and pulmonary rehabilitation. Interpretation Disease severity, symptom burden, gender, and disease treatments are associated with poor HRQOL. Recognition of these factors, treating symptoms, and consideration of palliative care may impact HRQOL in CTD-ILD.